The Role of Research Obsession in Shifting ChatGPT into a Plagiarism Tool - Hazaymeh, Omar (International Journal of Applied Research and Sustainable Sciences, 2024)
This research aims to investigate the dynamic landscape of artificial intelligence, with a particular focus on the consequences of the extensive utilization of ChatGPT's which participates in transformation it from a conversational language model to a potential tool that facilitates plagiarism for research purposes because of research obsession. As the digital age advances and with the increasing prevalence of academic dishonesty and content theft, there is a growing need for sophisticated tools to identify and fight plagiarism. As a result, the concerns about the ethical use of artificial intelligence are becoming increasingly important. This article examines the impact of research obsession on the development of ChatGPT and the unintended consequences that led to its misuse as a plagiarism tool. This study aims too to explore the underlying factors that have a part in this change, the ethical implications, and the possible remedies that can be used to help in to responsible AI development. The study hopes to contribute to the advancement of the discussion about plagiarism that depends on ChatGPT and enhance discussions on the responsible and ethical use of such technologies. By debating the effect of the research obsession on shifting ChatGPT to a tool for plagiarism, the study hopes to open new avenues for enhancing the integrity of academic and creative works in the digital era.